PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Sunarmie Sunarmie (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2016)
Every company contrives to get their officers engaged thoroughly to the company activities in form of absolute productivity to attain the objectives of the company. Meanwhile there are a lot of factors that may affect the productivity of the officers such as work spirit, discipline, level of education, skill, nutrition and health, attitudes, ethics, motivation, work climate, technology, production facilities, opportunities to work and accomplish something at work. The objectives of this research were to discover how motivation possibly affects the productivity of The Local Water Company (PDAM) officers in Palangka Raya at work and to find out which is the dominant variable that affects that productivity of The Local Water Company (PDAM) officers in Palangka Raya. Based on the regression analysis of the five work motivation variables towards work productivity, the research resulted on physiological need (X1), the need of security (X2), social need (X3), the need for achievement (X4), and the need for self-actualization (X5).  Furthermore, the most dominant variable that affected the productivity at work is the need of security which is 0.720, for the officers need an assurance of their safety in undertaking their tasks at work.